The Influence of Learning Independence and Learning Styles on the Chemistry Achievement of 11th-Grade Students at SMAN 2 Pasarwajo - Dahlan, Dahlan; Nurlansi, Nurlansi; Susilawati, Lastri (Universitas Pendidikan Mandalika, 2025)
This study aimed to describe students' learning independence, learning styles, and analyze their influence on chemistry learning achievement. The population as well as sample in this study were 42 students from classes XI.C and XI.D SMA Negeri 2 Pasarwajo in the 2024/2025 academic year. Questionnaire was used to obtain data of learning independence and learning styles, while learning achievement was obtained from semester test scores. Techniques of data analysis employed were descriptive and inferential statistical analysis, namely multiple linear regression analysis using dummy variables. The results showed that students' learning independence was in the moderate category (85.71%). Students' learning styles consisted of visual (21.43%), auditory (14.28%), kinesthetic (21.43%), and other combined styles. Meanwhile, students' learning achievement was in the moderate category (80.95%). Learning independence and learning styles influenced the chemistry learning achievement, both partially and simultaneously. Partially, learning independence contributed 35.3% and learning style namely visual, auditory, and kinesthetic sequentially contributed 19.9%, 10.4%, and 7.3%. Simultaneously, they contributed 72.9% to chemistry learning achievement.